The Role of the Association of Farmers Groups (Gapoktan) through the Cooperative Farming Model in advancing the Economy of Rural Communities - Hidayat, Yusuf; Nur, Rahmat; Muhammad Sabiri, Ahmad; Rachmah, Maulida; Maulana, Rama (Journal of Economics Education and Entrepreneurship, 2023)
The purpose of this study is to describe the role of Gapoktan through the Cooperative Farming Model in Karang Indah Village, Mandastana District, Barito District, Kuala Kalimantan. Describe the Gapoktan Karang Indah Program in advancing the community's economy, describing. Describe the impact of the Gapoktan program through cooperative farming. This type of research is qualitative research with a description approach. Research Instruments with Quantitative data through self-researchers (Human Instruments). Sources of data through interviews, observations and documentation. Qualitative data analysis consists of data reduction, data display and drawing conclusions. The validity of the data through triangulation. The results showed that (1) the Cooperative Farming Model plays a role in the management of rice entrepreneurs in expediting the distribution of rice commodities and encouraging the development of sustainable agricultural development. (2) The Gapoktan program in Karang Indah for rice farmers consists of socialization, partnership programs (government and private), and entrepreneurial agriculture-based training. (3) Gapoktan through the Cooperative Farming Model has a real impact on increasing rice farmer household income with the help of capital and financing. The use of the Cooperative Farming Model has a positive and significant impact in terms of the pattern of economic life of the Karang Indah village community.